Eicosapentaenoic acid free fatty acid prevents and suppresses colonic neoplasia in colitis‐associated colorectal cancer acting on Notch signaling and gut microbiota. Issue 9 (28th March 2014) - Piazzi, Giulia; D'Argenio, Giuseppe; Prossomariti, Anna; Lembo, Vincenzo; Mazzone, Giovanna; Candela, Marco; Biagi, Elena; Brigidi, Patrizia; Vitaglione, Paola; Fogliano, Vincenzo; D'Angelo, Leonarda; Fazio, Chiara; et al.
<x xml:space="preserve">Abstract</x> Inflammatory bowel diseases are associated with increased risk of developing colitis‐associated colorectal cancer (CAC). Epidemiological data show that the consumption of ω‐3 polyunsaturated fatty acids (ω‐3 PUFAs) decreases the risk of sporadic colorectal cancer (CRC). Importantly, recent data have shown that eicosapentaenoic acid‐free fatty acid (EPA‐FFA) reduces polyp formation and growth in models of familial adenomatous polyposis. However, the effects of dietary EPA‐FFA are unknown in CAC. We tested the effectiveness of substituting EPA‐FFA, for other dietary fats, in preventing inflammation and cancer in the AOM‐DSS model of CAC. The AOM‐DSS protocols were designed to evaluate the effect of EPA‐FFA on both initiation and promotion of carcinogenesis. We found that EPA‐FFA diet strongly decreased tumor multiplicity, incidence and maximum tumor size in the promotion and initiation arms. Moreover EPA–FFA, in particular in the initiation arm, led to reduced cell proliferation and nuclear β‐catenin expression, whilst it increased apoptosis. In both arms, EPA‐FFA treatment led to increased membrane switch from ω‐6 to ω‐3 PUFAs and a concomitant reduction in PGE2 production. We observed no significant changes in intestinal inflammation between EPA‐FFA treated arms and AOM‐DSS controls. Importantly, we found that EPA‐FFA treatment restored the loss of Notch signaling found in the AOM‐DSS control and resulted in the enrichment of Lactobacillus species in the gut microbiota. Taken together, our data suggest that EPA‐FFA is an excellent candidate for CRC chemoprevention in CAC.